Pemilihan Perumahan Idaman dengan Penerapan Metode Weighted Product - AR Walad Mahfuzhi; Sandhy Fernandez; Dandi Sunardi (Journal of Information System Research (JOSH), 2022)
Home is a basic need for every human being. Each house will function as a place to live or as a place to rest and a place of protection from various outside disturbances. Based on the needs of every human being for the house, developers compete in providing houses with their respective advantages and disadvantages in order to attract consumers or buyers to buy the house, and prospective buyers are also faced with various choices, including house prices, house locations, and house models. And various choices that will affect the choice of a dream home. With the existing problems, it is necessary to design a decision support system that is designed with an incremental model. The method used in order to provide a recommendation is the weighted product method. With the existing problems, this study aims to provide recommendations for which housing to be chosen by consumers. The results obtained in this study in the form of calculations using the weighted product method, it was found that a company named PT Berkah Prosperous as a housing company had the highest preference weight value of 7.35852. With these results obtained, the first recommendation for determining the ideal housing was chosen from the company PT Berkah Sejahtera.